تحسين جدولة عمل الممرضات باستخدام البرمجة الخطية بأعداد صحيحة دراسة حالة بالمؤسسة العمومية الاستشفائية بتابلاط ولاية المدية: Nurse Scheduling Optimization Using Integer Linear Programming - A Case Study at Tabelat Public Hospital Institution, Medea Province - قريشي أحمد,; بن يحي ثاني نسرين, (Journal of North African Economies, 2025)
The process of allocating nurses to tasks in healthcare centers presents a significant challenge, especially when relying on manual methods. These methods suffer from numerous drawbacks, including a high probability of errors, wasted time and efforts, and costs associated with inefficient allocation, ultimately impacting the center's efficiency and the quality of patient care. This research paper aims to highlight the role of Integer Linear Programming as a crucial tool in operations research and applied mathematics. It specifically focuses on how healthcare administrators can use ILP to address the nurse scheduling problem, leading to optimal human resource allocation and better decision-making. We constructed a mathematical model using ILP to solve the nurse scheduling problem. The model was solved using the Win QSB software. The results demonstrated the significance of this quantitative approach, as it achieved an optimal distribution of nurses, contributing to improved service quality and reduced costs. Key words: integer linear programming, nurse scheduling, resource allocation